2018
DOI: 10.1007/s11250-018-1633-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on piglet production/performance parameters

Abstract: Heat stress is problematic for pigs raised in tropical environments. The animal is large and has proportionally high body heat, and subcutaneous fat thickness reduces the animal's ability to thermoregulate. It is not clear how stress affects pig litter size. For this reason, we performed a meta-analysis of the effect of heat stress on pig litter size. We reviewed behavioral, endocrine, and cellular data and the signaling pathways involved in heat stress. We found that heat stress did not affect litter size or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
1
6
0
3
Order By: Relevance
“…It is known that cold environments decrease BW to maintain body temperature (Bal et al, 2016; Morrison et al, 2008), and heat stress reduces the accretion of muscle protein and developmental rate (Guo et al, 2018; Liu et al, 2022). Neonatal pigs need to maintain a warm temperature: a thermoneutral zone of 30–34°C, and the early period is extremely affected by temperature conditions; for example, heat and cold shock, because they do not have adequate muscle and fat tissue to adapt to the ambient environment (Carroll et al, 2012; Herpin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that cold environments decrease BW to maintain body temperature (Bal et al, 2016; Morrison et al, 2008), and heat stress reduces the accretion of muscle protein and developmental rate (Guo et al, 2018; Liu et al, 2022). Neonatal pigs need to maintain a warm temperature: a thermoneutral zone of 30–34°C, and the early period is extremely affected by temperature conditions; for example, heat and cold shock, because they do not have adequate muscle and fat tissue to adapt to the ambient environment (Carroll et al, 2012; Herpin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In general, commercial pig breeds are sensitive to environmental changes, and seasonal changes in temperature reduced their physiological functions such as development rate, metabolism and fertility (Carroll et al, 2012; Choi et al, 2019; Claus & Weiler, 1994; Guo et al, 2018; Liu et al, 2022; Yu et al, 2021). Furthermore, heat and cold stresses induce several diseases such as pneumonia and hypothermia, and increase the mortality rate in the commercial pig (Carroll et al, 2012; Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress is an increasingly studied factor in many livestock species as climate change threatens to increase the number of periods with large temperature variations, and thus reduce animal health and agricultural productivity ( Guo et al, 2018 ; Alfonso et al, 2021 ; Wankar et al, 2021 ; Goel et al, 2022 ). Fast-growing chicken are particularly sensitive to heat stress due to the absence of sweat glands and limited development of cardiovascular and respiratory systems ( Brugaletta et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that sows subjected to temperatures above their thermal neutral zone (≥ 25°C–35°C) under controlled conditions showed negative effects on reproductive performance, including decreased litter size and an increase in the time interval between weaning and the next litter. Furthermore, the restoration normal body temperature of the sows is irregular [24].…”
Section: Introductionmentioning
confidence: 99%